Job Preferences of Dairy Farmers in Eastern Switzerland: A Discrete Choice Experiment - Markus Lips; Christian Gazzarin; Harry Telser (German Journal of Agricultural Economics (GJAE), 2016)
Using a discrete choice experiment and a mixed-effects logit model, this article analyses the job preferences of 300 dairy farmers in the eastern part of Switzerland who intend to stay in milk production. The results show that a shift to suckler cow husbandry plus additional employment or to a job completely outside of agriculture would only be considered by dairy farmers in exchange for
Keywords: 330